Teachers’ Perception in Using a Blended Learning Method to Teach Listening Skill in EFL Classroom - Meisa Anastasia Yolanda; Hanif Nurcholish Adiantika; Dila Charisma (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2021)
In COVID-19 19 Pandemic, teachers have to be able to find the suitable learning methods to be used in teaching the students, especially in teaching listening skill. One of the contexts of methods is the blended learning method. Blended learning is the combination between traditional (face-to-face) learning and online learning. The main problem of the recent study is what is the teachers’ perception in using a blended learning to teach listening skill in EFL classroom. So, the research aimed at finding the teachers’ perception, their weaknesses and strengths in using blended learning method to teach listening skill in EFL classroom. This study employs a descriptive qualitative as a method. The participants of the study were two English teachers at one of vocational school in Cirebon. The data were collected through semi-structured interview to gain relevant data. The result of the research showed that in teachers’ perception; Teaching listening using online learning methods and blended learning is something new for both teachers and students. Several obstacles occurred, not only from difficulties in adapting to technology, several obstacles also emerged from various sides such as from student interest in learning and inadequate facilities for teachers. However, the use of blended learning is very helpful for teachers in teaching, especially in teaching listening during this pandemic, even though it is not optimal. Keywords: Teachers’ Perception; Blended Learning; Teaching Listening